A universal approach for optimizing charge extraction in electron transporting layer-free organic solar cells via Lewis base doping. Issue 45 (7th November 2019) - Wang, Rong; Wang, Boxin; Wang, Jianqiu; Zhang, Xuning; Zhang, Dongyang; Wei, Donghui; Sun, Xiaobo; Zhou, Huiqiong; Zhang, Yuan
Abstract : Applying anion-induced electron transfer doping with a series of TXABr salts to non-fullerene organic solar cells enables to tune the doping efficiency and photovoltaic device performance. Abstract : Although the improvement of power conversion efficiency (PCE) in organic photovoltaic cells (OSC) is due to the development of novel donors and non-fullerene acceptors, state-of-the-art devices commonly utilize charge transporting/extraction interlayers. Here we demonstrate a universal approach based on a series of tetraalkyl ammonium bromide (TXABr) Lewis bases as n-dopants for mediating electron extracting properties in a range of OSCs with non-fullerene or PCBM acceptors. Under optimal conditions, the TXABr-doped devices without electron transporting layers (ETLs) exhibit PCEs comparable to those of the ones based on a conventional device structure containing ETLs. We found that the doping efficiency of acceptors is intimately correlated with the chain length ( L chain ) of dopants. In OSCs based on acceptors of ITIC derivatives (IT-4F, ITIC, ITM, and ITCC), similar L chain -dependent doping efficiency and PCE modification are found, while for OSCs with acceptors bearing different structures in conjugated backbones or side chains, the selection rule of dopants to achieve the best performance enhancement is different. These correlations are explained by the mutual effects of electrostatic interaction in the dopants and steric hindrance between the dopants and acceptors, the latter of which is affected by the compatibility of side chains in the host and dopant. With TXABr doping, (quasi-)ohmic contacts for electrons are realized in these ETL-free devices, leading to expediting the charge sweepout with mitigated interfacial charge recombination. This work offers a promising pathway to realize high efficiency non-fullerene OSCs with simplified device architecture.